2013
DOI: 10.1002/andp.201200227
|View full text |Cite|
|
Sign up to set email alerts
|

Observational effects from quantum cosmology

Abstract: The status of quantum cosmologies as testable models of the early universe is assessed in the context of inflation. While traditional Wheeler-DeWitt quantization is unable to produce sizable effects in the cosmic microwave background, the more recent loop quantum cosmology can generate potentially detectable departures from the standard cosmic spectrum. Thus, present observations constrain the parameter space of the model, which could be made falsifiable by near-future experiments.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 87 publications
1
38
0
Order By: Relevance
“…However, on attempting to provide a finite prior for q 1 (and only in this context), we observe that most single field inflationary models generate a non zero tensor to scalar ratio and, therefore, we shall assume it varies in the interval [10 −4 , 0.8] . Given all such assumptions ,the prior for q 1 can be estimated to be [0,21].…”
Section: Discussionmentioning
confidence: 99%
“…However, on attempting to provide a finite prior for q 1 (and only in this context), we observe that most single field inflationary models generate a non zero tensor to scalar ratio and, therefore, we shall assume it varies in the interval [10 −4 , 0.8] . Given all such assumptions ,the prior for q 1 can be estimated to be [0,21].…”
Section: Discussionmentioning
confidence: 99%
“…The associated gravitational wave spectrum was studied in [46,62,63], while the scalar spectrum and the full set of linear-order cosmological observables were found in [48]. Observational consequences and subsequent constraints on the quantum corrections were finally studied in [15,52,64,65].…”
Section: Perturbations With Inverse Volume Correctionsmentioning
confidence: 99%
“…Loop quantum cosmology (LQC) is a quantum theory inspired by LQG that takes into account the cosmological symmetries. Some recent reviews can be found, e.g., in [11][12][13][14][15][16][17][18][19][20][21][22]. The status of perturbations in LQC is still not fully clear.…”
Section: Introductionmentioning
confidence: 99%